New Route to the Synthesis of 2-Phenylimino-3-γ-Picolinoyl-5- Aryl/ Alkylimino 1,3,4-Thiadiazolidines - Bhaskar, C.S.; Berad, B.N. (Asian Journal of Chemistry, 2010)
The synthesis of 2-phenylimino-3-γ-picolinoyl-5-aryl/alkylimino-1,3,4-thiadiazolidines (IV) is reported by a new route. The interaction of 1-γ-picolinoyl-4-aryl/alkyl thiosemicarbazides (I) and N-phenyl isocyanodichloride (II) on refluxing with chloroform medium for 1 h afforded (III) which on basification with dilute ammonium hydroxide solution gave the title compound (IV). The title compound on acetylation produced an acetyl derivative (V).